Détermination d’une ligne de rivage de grande taille à l’aide de la multi résolution hiérarchique sur une image RSO - Alain Akono (Unité Mixte de Recherche 8504 Géographie-cités, 2007)
The goal of this study is to evaluate the coastline length on a series of images reduced by the hierarchical multiresolution technique and extracted from a synthetic aperture radar image (SAR) of theERS-1 satellite, of very great size. In this study, the edge detection technique and the mathematical morphology are joined to the multiresolution technique to reach the targeted goal. The obtained results on the reduced images are then extrapolated in order to obtain the coastline length on the original image. The presented methodology allows getting good estimations of coastline lengths from great size satellite images, and it is particularly useful to the follow-up of the coast erosion process.